Automatic frequency tuning wireless charging system for enhancement of efficiency. Issue 24 (1st November 2014) - Kar, D.P.; Nayak, P.P.; Bhuyan, S.; Panda, S.K.
Abstract : An automatic frequency‐tuned wireless charging system is proposed and successfully demonstrated to enhance the power transfer efficiency for different vertical spacings between the charging coils in the presence of proximal metallic objects. The frequency characteristics of wireless power transfer efficiency have been investigated through simulation and experimental measurements. It has been observed that the resonance‐based wireless charging system is very sensitive to the imperfect positioning of charging coils and nearby metallic objects. At the operating frequency, the power transfer efficiency of the charging system reduces drastically. However, by allowing the transmitting frequency to adapt to the position of the coils and metallic objects through the automatic frequency‐tuned system, the deteriorated power transfer efficiency is further improved.